AKTUALISASI DIRI TOKOH SAYURI DALAM NOVEL TERJEMAHAN MEMOAR SEORANG GEISHA KARYA ARTHUR GOLDEN:KAJIAN KEBUTUHAN BERTINGKAT ABRAHAM MASLOW (Self-Actualization of Sayuri Character in Translated Novel Memoir of a Geisha by Arthur Golder: Study of Abraham Maslow’s Hierarchy of Needs) - M. Oktavia Vidiyanti (SAWERIGADING, 2015)
A work of Arthur Golden is chosen because the story in translated novel Memoir of a geisha could enlighten about the importance of finding some one’s identity in order to make the character could run his life in pride and could give the guidance and meaning in his life. The purpose of writing is to uncover the process of hierarchy needs motivation of Sayuri’s actualization in Memoir of a geisha by Arthur Golden at the beginning, fighting era, and successful era of being a geisha. It uses structure and literary content approaches. Structureapproach analyzes intrinsic aspect like narrator and character whilst literary content approach uses extrinsic aspect of hierarchy needs of Abraham Maslow. Using literary content analysis, suffering and achievement of Maslow needs hierarchy of women character named Sayuri is shown. The main conclusion of the writing emphasizes that someone could give meaning and accepts himself for whom he is with forging inn his life to find out his identity.